2001
DOI: 10.1093/jnci/93.4.266
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Hypoxia: Definitions and Current Clinical, Biologic, and Molecular Aspects

Abstract: Tissue hypoxia results from an inadequate supply of oxygen (O(2)) that compromises biologic functions. Evidence from experimental and clinical studies increasingly points to a fundamental role for hypoxia in solid tumors. Hypoxia in tumors is primarily a pathophysiologic consequence of structurally and functionally disturbed microcirculation and the deterioration of diffusion conditions. Tumor hypoxia appears to be strongly associated with tumor propagation, malignant progression, and resistance to therapy, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
1,809
3
18

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 2,350 publications
(1,866 citation statements)
references
References 107 publications
36
1,809
3
18
Order By: Relevance
“…No studies measuring O 2 tension in breast carcinoma in relation to patient survival have been published; however, in patients with cervical carcinoma, it is known that in vivo intratumoral hypoxia predicts poor survival. 1 In the current study and in our previous report, 19 HIF-1␣ staining often was observed in viable cells surrounding areas of necrosis, suggesting that hypoxia contributes to HIF-1␣ up-regulation in breast carcinoma. Adaptation to hypoxia is mediated by HIF-1, which stimulates angiogenesis (through VEGF) and high and anaerobic metabolism (through glucose transporters and glycolytic enzymes).…”
Section: Discussionsupporting
confidence: 72%
“…No studies measuring O 2 tension in breast carcinoma in relation to patient survival have been published; however, in patients with cervical carcinoma, it is known that in vivo intratumoral hypoxia predicts poor survival. 1 In the current study and in our previous report, 19 HIF-1␣ staining often was observed in viable cells surrounding areas of necrosis, suggesting that hypoxia contributes to HIF-1␣ up-regulation in breast carcinoma. Adaptation to hypoxia is mediated by HIF-1, which stimulates angiogenesis (through VEGF) and high and anaerobic metabolism (through glucose transporters and glycolytic enzymes).…”
Section: Discussionsupporting
confidence: 72%
“…The advantages of PDT are that it is a noninvasive treatment and the generated reactive oxygen species (ROS) have a short lifetime and diffusion range (0.1 µm); treatment at restricted sites is therefore possible 2, 3. However, PDT also has some drawbacks as a first‐line therapy because its effectiveness is reduced when the oxygen supply is lowered in tumors due to their microvessel structure and microcirculation, and because of oxygen consumption by the PDT process 4. In addition, PDT agents may cause genetic variation when they are taken up by organelles such as the nucleus 5.…”
Section: Introductionmentioning
confidence: 99%
“…For locally advanced solid tumors, hypoxia is a characteristic property due to rapid cancer cell proliferation, high metabolic demands, and functional angiogenesis 8. There is clear evidence that hypoxia can promote cancer development and it is involved in the resistance to treatment via the formation of new blood vessels 9.…”
Section: Introductionmentioning
confidence: 99%